2010
DOI: 10.1186/alzrt30
|View full text |Cite
|
Sign up to set email alerts
|

A novel Aβ isoform pattern in CSF reflects γ-secretase inhibition in Alzheimer disease

Abstract: IntroductionLY450139 (semagacestat) inhibits γ-secretase, a key enzyme for generation of amyloid β (Aβ), the peptide deposited in plaques in Alzheimer disease (AD). Previous data have shown that LY450139 lowers plasma Aβ, but has no clear effect on Aβ1-40 or Aβ1-42 levels in cerebrospinal fluid (CSF). By using targeted proteomics techniques, we recently identified several shorter Aβ isoforms, such as Aβ1-16, that in experimental settings increase during γ-secretase inhibitor treatment, and thus may serve as se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 30 publications
5
43
0
Order By: Relevance
“…Altogether 33 different Aβ peptides were identified (SI Appendix, Table S1) some of which, e.g., Aβ1-15, previously identified as a positive biomarker of γ-secretase inhibition (22,23), constituted less than 1% of the total ion current chromatogram. No sign of any glycosylated derivatives of Aβ1-40 (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Altogether 33 different Aβ peptides were identified (SI Appendix, Table S1) some of which, e.g., Aβ1-15, previously identified as a positive biomarker of γ-secretase inhibition (22,23), constituted less than 1% of the total ion current chromatogram. No sign of any glycosylated derivatives of Aβ1-40 (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Second, for the first time we show that ␥-secretase catalyzed processing at every third or fourth amino acid continues beyond A␤40 and A␤38 and we show how this mechanism results in major shorter A␤ peptides including A␤30, A␤31, A␤34, A␤37, and A␤39. Third, we identify A␤34 as a major convergence point for the product lines, which may also explain the particular sensitivity of this A␤ species in recent human trials with two different ␥-secretase inhibitors (19,24). Fourth, and perhaps most importantly, we identify cross-talks between the major A␤ product lines, and several novel reactions resulting in A␤46 -43, A␤42-40, A␤40 -38, and A␤40 -37 and that directly impact A␤40 and A␤42 production opening up new opportunities for modulation of A␤42 production and the A␤42/40 ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Minor cleavage events result in cross-talks between the major routes and alternative pathways to modulate A␤42 production and the A␤42/40 production ratio (hatched arrows). The major processing routes converge at A␤34, which is further hydrolyzed by ␥-secretase resulting in A␤30, which is the shortest BACE and ␥-secretase-dependent A␤1-x peptide identified in human CSF (19). All peptides (arrows) are written in CàN-terminal direction.…”
Section: Discussionmentioning
confidence: 99%
“…PP-2A can reduce the phosphorylation level of APP and it was reported that the rise of the phosphorylation level of APP could increase the Aβ generated (26). Up to now, people still have not been well aware of the pathogenesis of AD but the majority of the scholars have stated that Aβ deposition was the common approach for all factors causing AD (27).…”
Section: Discussionmentioning
confidence: 99%